The effect of FED's quantitative easing policy on listed companies and sectors in South Africa - Chacha, Terry (Department of Finance and Tax, 2017)
This paper examines the effect of Quantitative Easing (QE) on listed companies and sectors in South Africa. The unconventional monetary policy carried out by the developed markets had spill over effects in emerging market economies. We focus on the policies performed by the United States. Our interest is to find out whether the QE announcements had any impact on the returns of listed companies and sectors in South Africa. An exploratory analysis is done on the macroeconomic and financial indicators in SA to provide grounds for doing the analysis on the listed companies. This analysis shows that the exchange rate and portfolio inflows were impacted by QE. However, other local factors were in play in affecting the exchange rate. The shrinkage in the global economic activity affected the Gross Domestic Product (GDP) growth rate. The changes in inflation cannot be attributed to QE. Most of the portfolio inflows were in the bond market and since some were directed to the equity market we proceed to check whether stocks and sectors had abnormal returns as a result. Our empirical analysis shows that only three companies had significant Cumulative Abnormal Returns (CARs) in the three phases of QE. On the sector front, nine out of the 34 sectors had significant CARs every time QE was announced. A broader classification of these sectors into industries shows that the industries represented are industrials, consumer goods, consumer services and financials. In QE1, the industrials industry and the consumer services industry had negative CARs but in QE2 and QE3, they had positive CARs. The consumer goods industry had positive CARs during the three phases of QE. This research concludes that QE1 had the greatest impact on the Johannesburg Stock Exchange (JSE) and its impact was negative. QE2 had a positive impact on the JSE since most companies and sectors had significant positive CARs. The impact of QE3 on sector abnormal returns was almost neutral. We also provide an investment strategy on the JSE using various indices for the periods following QE2 and QE3. Out of the 14 indices used, the small caps index is given a higher weighting in both portfolios due to its low risk.